SISTEM MONITORING DAN EVALUASI KEGIATAN BELAJAR MENGAJAR (E-MONEV KBM) BERBASIS WEB - Sahmad; Tomy Dwi Cahyono; M. Julkarnain (Program Studi Informatika Universitas Teknologi Sumbawa, 2019)
As an organizer of technology-based academic activities, Sumbawa University of Technology wants to utilize technology as the main support for activities on campus. One of the activities that require technological touch is the process of monitoring and evaluation in lecturing activities. Vice Chancellor I in the academic field as the part that oversees the implementation of lectures, so far the system that is carried out in monitoring lectures is still classified as manual, namely by assigning staff to check each lecture room. From the current system, it is considered inefficient because it requires a lot of checking personnel to remember the number of lectures that occur at one time. Therefore the solution used to overcome this is to create a computerized system that can facilitate the process of monitoring and evaluation so as to reduce the need for personnel and time. Therefore the aim of this research is to develop a web-based monitoring and evaluation system of teaching and learning activities (E-Monev). This system was developed using the PHP programming language by using the Codeigniter and Mysql framework as a database and using the waterfall method in application development